Study of Alpha Particle Impact Double Ionization Cross Sections of Cu Atom - Gupta, S. P.; Yadav, K.; Ghimire, R.; Khanal, R.; Jha, L. K. (Journal of Nepal Physical Society, 2021)
Semi-classical binary encounter approximation has been used for the study of ionization cross sections of Cu atom at ground state. Projectile, alpha particle, with energy varying from threshold to 360 keV/amu are considered for direct double ionizations cross section. Out of the two path ways of ionization we have ruled out the indirect process (like excitation-auto ionization, Auger effect) of double ionization. We considered direct - ionization of outer shells of Cu atom. Vriens accurate expression of cross section for energy transfer ΔE(σΔE ) and Hertree-Fock velosity distribution function for the target electrons are used. The theoretical value of double ionization cross sections at impact energy 300 keV/amu is 0.98 x 10-16 cm2 which is same as experimental values at that impact energy. Above energy of 300 keV/amu, the calculated results underestimates the experimental data and at 360 keV/amu their magnitude are 0.77 x 10-16 and 1.0 x 10-16 respectively. Above impact energy of 75keV/amu, all the theoretical results have ratio factor within 2. Out of the total number of theoretical data 75% are under valid range of ratio factor 2 and among the valid range 41% have ratio factor below 1.325 and hence calculated results of double ionization cross section lie in the acceptable range. The linear correlation coefficient (R square) and standard deviation (SD) of linear fit are 0.6984 and 0.7883 respectively. In low energy range the theoretical results are more apart from corresponding experimental values and possess relatively more error compared to intermediate and higher energy region. Calculated results are in satisfactory agreement with experiment in intermediate and high energy range.